Case Report: Perivascular epithelioid tumors of the gastrointestinal tract - Yan, Hui; Zhang, Shuhui; Ba, Ying; Li, Kun; Gao, Guoling; Li, Yanmin; Zhang, Yan; Liu, Chengxia; Shi, Ning (Frontiers in Oncology, 2023)
Introduction: Perivascular epithelioid cell tumor of the gastrointestinal tract (GI PEComa) is a rare mesenchymal neoplasm. GI PEComa is mostly seen in the colon in a marked middle-aged female predominance. PEComa has no typical clinical manifestations, imaging manifestations, or endoscopic characteristics. Therefore, the diagnosis of this disease mostly relies on the pathology findings. HMB-45 is the very sensitive immune marker of PEComa. Case report: We reported a case of a middle-aged female with sigmoid colon PEComa. To exclude carcinogenesis, the large basal polyp in the sigmoid colon was removed by endoscopic mucosal resection (EMR). This lesion expressed HMB-45+ as the characteristic melanin marker of PEComa in immunohistochemistry analysis. Finally, we made a diagnosis of sigmoid colon PEComa. At present, surgical resection is the primary treatment for PEComa. Though the characteristics of tumor biology and clinical behavior in PEComa are not clear, the boundary is clear to be fully removed. However, close follow-up is required after the surgery because of the lesion's undetermined benign and malignant nature. Discussion: The present case study emphasizes the importance of pathological diagnosis. Therefore, upon finding gastrointestinal polyps with a mucosal ulcer under endoscopy, the GI PEComa diagnosis should be considered. It is necessary to detect characteristic melanin markers of PEComa. Due to the rarity of cases, great challenges are being faced in diagnosing and treating PEComa.